VILLAGE FUND MANAGEMENT ACCOUNTABILITY MODEL: THE ROLE OF INTERNAL CONTROL AND ORGANIZATIONAL CULTURE - Nonce Farida Tuati; Abdul Halik; Siti Mujanah; Deetje W. Manuain; Hapsa Usman (Politeknik Negeri Ambon, 2026)
Introduction: The purpose of this study is to analyze the influence of internal control and organizational culture on the accountability of village fund management in Taibenu District. The urgency of this research is to provide input to increase accountability in village fund management, provide information for improving policies related to village funds, and increase understanding of the importance of accountability in village fund management. Methods: This study is a quantitative study using primary data obtained by respondents. The data analysis techniques used include the classical assumption deviation test and multiple regression analysis as well as the T test and the F test. While the multiple regression equation model used in this study is: Y = a + b1X1 + b2X2 + e, Results: The results of the study show that good internal control and organizational culture partially and simultaneously have a positive and significant effect on the accountability of village fund management. With the results of the t test = 3.722 with p = 0.001 < 0.05 and the t test = 2.467 with p = 0.022 <0.05 and the F test showed a calculated F value of 24.602 with a significance level of p = 0.000 < 0.05. Keywords: Accountability, Internal Control, Organizational Culture, Village Fund